Qualification of Sanctions for Money Laundering Crimes from the Proceeds of Narcotics Crimes - Hamdan H. Rampadio (Indonesian Research Journal in Legal Studies, 2025)
This research aims to examine and analyze the application of criminal sanctions for perpetrators of money laundering offenses arising from narcotics crimes. This study employs normative legal research, focusing on the criminal sanction system applied to money laundering offenders originating from narcotics-related proceeds. The research uses a normative approach based on primary, secondary, and tertiary legal sources, including court decisions, and conducts qualitative analysis through legal reasoning and argumentation. The results indicate that the criminal sanctions imposed on perpetrators of money laundering from narcotics proceeds are considered very light and inconsistent with the objectives of justice and the enforcement of laws regulating the eradication of money laundering and narcotics offenses. The sanctions are deemed excessively lenient because the acts are treated as a single offense, despite the perpetrators committing a combination of multiple offenses (concursus and voorzette delict). Moreover, the Public Prosecutor’s Office does not process co-perpetrators (medeplegen) as responsible parties, even though they are proven to have participated in the commission of money laundering offenses related to narcotics crimes (predicate offenses). Additionally, the judges’ considerations in sentencing the perpetrators do not adequately take into account the legal facts revealed during trial, the evidence presented by the public prosecutor, or the legal reasoning from both the judex facti and judex juris perspectives. Consequently, the sanctions imposed are very light and deviate from the criminal sanction system stipulated in the Indonesian Penal Code (KUHP) and established doctrines of criminal law in Indonesia. The recommendations of this study are, first, to strengthen law enforcement regarding narcotics and money laundering crimes, including enhancing the capacity to detect and investigate money laundering derived from narcotics proceeds; and second, for judges to continuously improve their expertise, gain practical experience, and carefully assess which legal provisions are applicable. This will enable them to analyze relevant factors effectively and ensure that judicial decisions are fair, consistent, and grounded in legal reasoning.